2006
DOI: 10.1007/s10682-005-5379-x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Consequences of Clonal Growth in Stenocereus eruca, a Rare Clonal Cactus of the Sonoran Desert

Abstract: Stenocereus eruca is a prostrated, self-incompatible cactus endemic to the Sonoran Desert that regenerates primarily through clonal propagation. Clonal growth is expected to affect mate availability by influencing the number and spatial distribution of mating types. In this paper we examine the role of clonal growth on female fecundity through a series of pollination experiments in a population of S. eruca. We set up a pollen supplementation experiment using five distance treatments with pollen collected at 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
(39 reference statements)
1
14
0
Order By: Relevance
“…6, 7). This result indicates the negative effects of both tree enlargement and clonal growth on female reproductive success, which has been shown in several clonal plants (Eriksson and Bremer 1993;Eckert 2000;Wolf et al 2000;Wang et al 2005;Clark-Tapia et al 2006). Unfortunately, the full range of genet size variation in the plot was not investigated because the maternal trees were sampled from only two genets with clonal trees.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…6, 7). This result indicates the negative effects of both tree enlargement and clonal growth on female reproductive success, which has been shown in several clonal plants (Eriksson and Bremer 1993;Eckert 2000;Wolf et al 2000;Wang et al 2005;Clark-Tapia et al 2006). Unfortunately, the full range of genet size variation in the plot was not investigated because the maternal trees were sampled from only two genets with clonal trees.…”
Section: Discussionmentioning
confidence: 97%
“…After Charpentier (2001), some empirical studies investigated the relationship between clonal growth and reproductive success (Reusch 2001;Routley et al 2004;Wang et al 2005;Wilson et al 2005;Clark-Tapia et al 2006;Trapnell and Hamrick 2006). These studies often demonstrated that female reproductive success decreased with clonal growth due to geitonogamy but rarely examined male reproductive success using molecular markers.…”
Section: Introductionmentioning
confidence: 99%
“…† Within-vs. between-population crosses. Fitness of progeny from within-population crosses can be greater than, equal to or less than that of those from between-population crosses, and it may vary between populations and fitness traits (Riley, 1956;van Treuren et al, 1993;Hauser and Loeschcke, 1994;Dahlgaard and Warncke, 1995;Trame et al, 1995;Fischer and Matthies, 1997;Byers, 1998;Richter and Weiss, 1998;Affre and Thompson, 1999;Sheridan and Karowe, 2000;Emery and McCauley, 2002;Luijten et al, 2002;Colling et al, 2004;Heliyanto et al, 2005;Becker et al, 2006;Busch, 2006;Ricardo et al, 2006;Billingham et al, 2007;Willi et al, 2007;Cañ o et al, 2008;Raabová et al, 2009;Forrest et al, 2011). In a meta-analysis, Angeloni et al (2011) found that d did not vary between intra-and interpopulation crosses, which indicates that neither outbreeding depression nor heterosis commonly occurs as a result of crosses between populations.…”
Section: Theoretical Aspectsmentioning
confidence: 99%
“…V. myrtillus, V. uliginosum and V. vitis-idaea are clonal plant species which reproduce generatively (predominantly by outcrossing) and vegetativelly (through rhizomes). In such species, an increase in levels of genetic diversity depends on the efficiency of the production of out-crossed seeds and mobilization of generatively reproduced plants (Eriksson 1989;Eriksson and Fröborg 1996;Persson and Gustavsson 2001;Albert et al 2004), while clonal propagation reduces levels of out-crossing, the formation of new genetic combinations (Charpentier 2002;Honnay and Bossuyt 2005) and ultimately levels of genetic diversity through the prevalence and domination of more competitive genotypes (genets) which are more efficient in producing ramets (Eriksson 1989(Eriksson , 1993Jacquemart et al 1994;Pornon et al 2000;Honnay and Bossuyt 2005;Clark-Tapia et al 2006). Although lower levels of genetic diversity are generally expected in clonal plant species (Hamrick and Godt 1989;Bartish et al 1999;Nybom and Bartish 2000), several studies revealed as much genetic diversity in clonal as in non-clonal plants (Ellstrand and Roose 1987), and this holds also for Vaccinium species (e.g.…”
Section: Introductionmentioning
confidence: 99%